Sub maximal oxygen uptake related to fat free mass and lean leg volume in trained runners. Issue 4 (December 1976) - Winter, E. M.; Hamley, E. J.
Abstract : The sub maximal oxygen uptake (VO2) of 32 trained male middle and long distance runners aged 19.5-36.0 years was determined at five treadmill speeds. There was a significant linear relationship (p less than 0.01) between VO2 at each of the treadmill speeds and Fat-Free Mass (FFM) and Lean Leg Volume (LLV). To explain the relationship other factors are considered, the most important of which may be the mechanical configuration of muscle and mitochondrial function.